El tabaco y las periodontopatías. - Dini, E. L.; Coelho Guimaraes, L. O. (My University, 1995)
The purpose of this research, which is part of a study on periodontal disease and its risk factors among workers in Araraquara, São Paulo, Brazil, was to determine the association between smoking and its frequency, on the one hand, and the presence of periodontal cavities on the other. A sample of 528 sugar and alcohol refinery employees from Araraquara between the ages of 18 and 64 was examined in March and April of 1992 by a trained examiner who applied the Index of Periodontal Treatment Needs in the Community. Questionnaires were used to record the individuals' age, smoking habits, and the number of cigarettes smoked daily. An oral examination was also performed to assess the presence of dental plaque and to determine the bacterial colony index. Data analysis revealed a positive association between the presence of periodontal cavities and smoking. After adjusting the data for age, presence of dental plaque, and bacterial colony index, the odds ratio for having periodontal cavities increased directly with the number of cigarettes smoked. These results suggest that smoking and its frequency should be taken into account when planning programs for the primary prevention and treatment of periodontal disease.
Tobacco and periodontopathies
Keywords: adolescent; adult; age distribution; Brazil; female; human; male; periodontal disease; periodontics; risk; risk factor; smoking; statistical model; tooth calculus; tooth plaque; Adolescent; Adult; Age Distribution; Dental Calculus; Dental Plaque Index; English Abstract; Female; Human; Logistic Models; Male; Middle Age; Odds Ratio; Periodontal Diseases; Periodontal Index; Risk Factors; Smoking